Isolation and Identification of Yeast from the Fish Gut for Potential Application in Aquaculture - Ravendra Mishra (KUFOS, 2018)
Abstract- The probiotic properties of yeasts have been scarcely reported in aquaculture compared to the bacterial probiotic. Fifteen yeast strains were isolated from the gastro intestinal (GI) tract of three important brackish water culture fishes, the Etroplus suratensis, Oreochromis moassambicus and Lates calcarifer. Among the 15 isolates many isolates exhibited varying enzyme activity and antibacterial activity against Vibrio harveyi. Based on the protein content the isolates E8 (28.4%), T4 (23.8%) and SB4 (36.8%) from the Etroplus suratensis, Oreochromis moassambicus and Lates calcarifer respectively were selected for identification and further analysis of probiotic potentials. E8, T4 & SB4 were identified by sequencing internal transcribed spacer (ITS) regions as Candida parapsilosis, Candida glabrata and Pichia Kudriavzevil respectively. Identity of the isolates were further confirmed by MALDI-TOF biotyping. The bile tolerance level of the three isolates was found to be ≤ 8% . The NaCI tolerance level was ≤3% for all the three isolates. Alkaline pH was found to be more favorable for all the three isolates than acidic and neutral pH. All the three isolates were found to be resistant to most of the antibiotics tested. To our knowledge this is the first attempt for isolation of yeast from the GI tract of Etroplus suratensis. With the high protein content (36.8%), bile tolerance and salinity tolerance the isolate Pichia Kudriavzevil can be of a promising candidate as gut probiotic/feed supplement in brackish/marine aquaculture.